Low‐load resistance exercise during inactivity is associated with greater fibre area and satellite cell expression in older skeletal muscle. Issue 4 (14th May 2018) - Moore, Daniel R.; Kelly, Ryan P.; Devries, Michaela C.; Churchward‐Venne, Tyler A.; Phillips, Stuart M.; Parise, Gianni; Johnston, Adam P.
Abstract: Background: Age‐related sarcopenia is accelerated by physical inactivity. Low‐load resistance exercise (LLRE) counters inactivity‐induced muscle atrophy in older adults, but changes in muscle fibre morphology are unstudied. We aimed to determine the impact of LLRE during short‐term inactivity (step‐reduction) on muscle fibre size and capillarity as well as satellite cell (SC) content in older skeletal muscle. Methods: Fourteen older (~71 years) male adults underwent 14 days of step reduction (<1500 steps/day) while performing six sessions of LLRE (~30% maximal strength) with one leg (SR + EX) while the contralateral leg served as an untrained control (SR). Seven healthy ambulatory age‐matched male adults (~69 years) served as a comparator group (COM). Muscle biopsies were taken from the vastus lateralis after 14 days, and immunohistochemical analysis was performed to determine muscle fibre cross‐sectional area (CSA), myonuclear content, SC content (PAX7 + cells), and total (C:F) and fibre type‐specific (C:Fi) capillary‐to‐fibre ratios. Results: Type I and II fibre CSA was greater in SR + EX compared with SR. Whereas there were no differences across fibre types between SR + EX and CON, type II fibre CSA was significantly lower in SR compared with COM. Type II myonuclear domain was greater in SR + EX compared with COM and SR. Pax7 + cells associated with type I and II fibres were lower in SR compared with SR + EX. Type II PAX7+ cells were also lower in SR compared with COM with a similar trend for type I fibres. There were trends for a lower C:Fi in SR compared with SR + EX for both fibre types with no differences for each compared with COM. Conclusions: Minimal LLRE during a period of decreased physical activity is associated with greater muscle fibre CSA, SC content, and capillarization. These results support the use of LLRE as an effective countermeasure to inactivity‐induced alterations in muscle morphology with age.